2012
DOI: 10.1371/journal.pone.0048137
|View full text |Cite
|
Sign up to set email alerts
|

High Risk HPV Contamination of Endocavity Vaginal Ultrasound Probes: An Underestimated Route of Nosocomial Infection?

Abstract: BackgroundEndocavity ultrasound is seen as a harmless procedure and has become a common gynaecological procedure. However without correct disinfection, it may result in nosocomial transmission of genito-urinary pathogens, such as high-risk Human Papillomavirus (HR-HPV). We aimed to evaluate the currently recommended disinfection procedure for covered endocavity ultrasound probes, which consists of “Low Level Disinfection” (LLD) with “quaternary ammonium compounds” containing wipes.MethodsFrom May to October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 16 publications
5
76
1
3
Order By: Relevance
“…One study, aimed at assessing the presence of HPV on frequently used equipment in gynecological practice (glove box, lamp of a gynecological chair, gel tubes for ultrasound, colposcope and speculum), found that 18% of samples were HPV positive, supporting the hypothesis of possible nosocomial transmission (Gallay et al, 2015). HPV transmission by endocavity vaginal ultrasound has been suggested, after high-risk HPV DNA was shown to persist on ultrasound probes despite disinfection with quaternary ammonium wipes and probe cover (Casalegno et al, 2012).…”
Section: Hygiene Measuresmentioning
confidence: 99%
“…One study, aimed at assessing the presence of HPV on frequently used equipment in gynecological practice (glove box, lamp of a gynecological chair, gel tubes for ultrasound, colposcope and speculum), found that 18% of samples were HPV positive, supporting the hypothesis of possible nosocomial transmission (Gallay et al, 2015). HPV transmission by endocavity vaginal ultrasound has been suggested, after high-risk HPV DNA was shown to persist on ultrasound probes despite disinfection with quaternary ammonium wipes and probe cover (Casalegno et al, 2012).…”
Section: Hygiene Measuresmentioning
confidence: 99%
“…However, these barriers have a perforation rate of 1-9% [53][54][55][56]. One study collected 217 samples before and 200 samples after the ultrasound examination [57]. After the ultrasound procedure, 3% of the samples contained high-risk HPV types (16,31,53,58) [57].…”
Section: Potential Routes and Evidence Of Non-sexual Transmissionmentioning
confidence: 99%
“…Une éventuelle contamination des sondes échogra-phiques par les HPV a été étudiée dans un service de gynécologie lyonnais [11]. La première partie de l'étude a été réalisée à partir de 200 échantillons collectés avec un écouvillon sec dans les 15 minutes suivant la désinfec-tion de la sonde après l'examen aux ultrasons avec une lingette contenant un ammonium quaternaire.…”
Section: Revue Critique Des éTudes Cliniques Récentesunclassified